A review on effectiveness between liquid and solid fertilizer towards the growth of oil palm in nursery / Ahmad Syafiq Norridzwan - Norridzwan, Ahmad Syafiq (Faculty of Plantation and Agrotechnology, 2017)
Oil palm has surpassed all business vegetable oil trims on the planet in oil generation. The key to the prosperity of oil palm in maintaining its profitability and supportability is because of good manure and sustenance administration. This review was carried out to examine the effectiveness between liquid and solid fertilizer in nursery towards the growth of oil palm. Fertilizer in form of solid and liquid is one of the best agricultural methods since it enhances fertility of soil and gives supplement to the oil palm tree. Through years of decades, good fertilizer and nutrition management of oil palm have become the priority and are continuously applied in all oil palm plantations throughout the world. However, the use of both sorts of manures in some cases can build the cost, prompt to contamination and diminish the compelling and effectiveness of compost application. Results show that liquid fertilizer is better for growth of oil palm seedling while solid fertilizer is more suitable in providing nutrient for oil palm’s productivity. Ultimately, the best fertilizer application is the combination of liquid fertilizer along with solid fertilizer because it will provide more benefit for the productivity of oil palm.